2003
DOI: 10.1161/01.cir.0000066319.56234.c8
|View full text |Cite
|
Sign up to set email alerts
|

Defibrillator Versus β-Blockers for Unexplained Death in Thailand (DEBUT)

Abstract: Background-Sudden Unexplained Death Syndrome (SUDS) is the leading cause of death in young, healthy, Southeast Asian men. The role of an implantable cardioverter defibrillator (ICD) for mortality reduction in these patients remains unclear. Methods and Results-The Defibrillator Versus ␤-Blockers for Unexplained Death in Thailand (DEBUT) study is a randomized, clinical trial conducted in 2 phases (pilot study followed by the main trial) to compare the annual all-cause mortality rates among SUDS patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(58 citation statements)
references
References 20 publications
0
56
0
2
Order By: Relevance
“…It is believed that BrS is an inherited disease attributed to genetic penetrance in family members. Currently, implantable cardioverter defibrillator (ICD) is the standard treatment for secondary prevention post‐SCA or syncope of unknown origin 5, 6. The ICD is an effective treatment to prevent cardiac arrest from recurrent ventricular tachycardia or ventricular fibrillation (VF) in BrS patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that BrS is an inherited disease attributed to genetic penetrance in family members. Currently, implantable cardioverter defibrillator (ICD) is the standard treatment for secondary prevention post‐SCA or syncope of unknown origin 5, 6. The ICD is an effective treatment to prevent cardiac arrest from recurrent ventricular tachycardia or ventricular fibrillation (VF) in BrS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The only proven effective treatment of BrS is prophylactic implantation of an automatic cardioverter-defibrillator (ICD) unit [Brugada et al, 2000a;Nademanee et al, 2003]. However, a recent study has shown that during a follow-up of 43 years, only 2.6% of a cohort of BrS patients received appropriate shocks, whereas 8.9% experienced device-related complications .…”
Section: Introductionmentioning
confidence: 99%
“…Beta Blockers in Unexpected Death in Thailand (DEBUT) trial, 86 patients who survived cardiac arrest or had a Brugada type electrocardiogram were randomized to beta blockers or prophylactic ICD implant. 23 After 3-year follow-up, there were four deaths that all occurred in the beta-blocker arm. There were seven patients in the ICD arm who had appropriately treated VF.…”
Section: Indicationsmentioning
confidence: 99%